2016
DOI: 10.1016/j.jpubeco.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Traffic accidents and the London congestion charge

Abstract: In a rare effort to internalize congestion costs, London recently instituted charges for traveling by car to the central city during peak hours. Although the theoretical influence on the number and severity of traffic accidents is ambiguous, we show that the policy generated a substantial reduction in both accidents and fatalities in the charged area and hours. At the same time, the spatial, temporal and vehicle specific nature of the charge may cause unintended substitutions as traffic and accidents shift to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 30 publications
3
70
1
Order By: Relevance
“…For example, Green et al (2014) examined monthly traffic accident counts, based on counts reported to the police in central London before and after the congestion charge compared to several suitable controls and found a substantial and robust decline in accidents associated with the advent of the congestion charge in London. The effect of congestion charging was in the order of a reduction of 34 accidents per month when compared to other cities.…”
Section: Accidentsmentioning
confidence: 99%
“…For example, Green et al (2014) examined monthly traffic accident counts, based on counts reported to the police in central London before and after the congestion charge compared to several suitable controls and found a substantial and robust decline in accidents associated with the advent of the congestion charge in London. The effect of congestion charging was in the order of a reduction of 34 accidents per month when compared to other cities.…”
Section: Accidentsmentioning
confidence: 99%
“…Only a small number of studies in public finance employed the synthetic control method (e.g., Mukherji and Mukhopadhyay 2011, Koehler and König 2015, Falkenhall et al 2015, Green et al 2016. 5 As the most related study, Hämäläinen and Moisio (2015) use the synthetic control method to evaluate the implementation of a second layer of local government in one region in…”
Section: Introductionmentioning
confidence: 99%
“…A congestion charge has been implemented in Stockholm [33] and London [34] with initially relatively good results, but it remains to be seen if their long-term impact will be positive. There are attempts to introduce tolls and fees, and differentiated road pricing schemes [35,36], in order to see if they can help in minimizing impact traffic congestion has on health and environment [37] and on drivers behavior [38] .…”
Section: The Problemmentioning
confidence: 99%